TEACHING THE EXPRESSION OF ASKING FOR AND GIVING OPINION BY USING FINDING A DATE GAME IN THE EIGHT YEAR OF SMP N 1 SEMANDING - Moch. Maskuri (Universitas PGRI Ronggolawe Tuban, 2024)
The purposes of the study was to know the process of teaching the expression of asking for and giving opinion by using finding a date game and the effectiveness of this game in teaching the expression of asking for and giving opinion This study used pre-experimental quantitative research one group pretest-posttest. The population & the sample of the study is the Eight Year Students of SMP N 1 Semanding The result of the study shows that the result of experimental study using statistical method called t-test and then tested using SPSS. The result of t count = -22.705 < t table = -2.0518. Because the value of t count is higher than the value of t table, it could be concluded that there is significant difference in the achievement between the students who are taught before the treatment and after the treatment and there is effectiveness in using finding a date game. It could be concluded also that finding a date game was an effective medium of teaching the expression of asking for and giving opinion